2020
DOI: 10.3390/ijerph17176135
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Prenatal Smoking Cessation Interventions among Public Health Nurses in Japan

Abstract: This study aimed to identify the factors associated with prenatal smoking cessation interventions based on the 5As model among public health nurses (PHNs) in Japan. A nationwide cross-sectional study was conducted from December 2019 to February 2020 via a self-administered questionnaire. The study subjects were 1988 PHNs working in 431 health centers of municipalities and special wards across the country. Of the 1988 questionnaires mailed, 521 responses (26.2%) were included in the analysis. Of the 521 respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 47 publications
0
10
1
Order By: Relevance
“…The present study largely supports these findings. At the same time, Li et al’s model found that public health nurses’ years of experience positively influenced self-efficacy, but years of nursing experience were not found to be a significant factor in the present study [ 19 ]; Chatdokmaiprai et al similarly found no relationship between self-efficacy and a nursing professional’s age or years of nursing experience [ 23 ].…”
Section: Discussioncontrasting
confidence: 55%
See 3 more Smart Citations
“…The present study largely supports these findings. At the same time, Li et al’s model found that public health nurses’ years of experience positively influenced self-efficacy, but years of nursing experience were not found to be a significant factor in the present study [ 19 ]; Chatdokmaiprai et al similarly found no relationship between self-efficacy and a nursing professional’s age or years of nursing experience [ 23 ].…”
Section: Discussioncontrasting
confidence: 55%
“…Exploratory factor analysis (maximum likelihood method, promax oblique rotation) was performed to identify latent variables for structural equation modeling. The observed variables consisted of a total of 20 items: six items on SCS behaviors, three items on SCS self-efficacy, ten items on attitudes and perceived importance of SCS, and, with reference to the results of Li et al, years as a nursing professional [ 19 ]. The analysis identified the four factors shown in Table 3 : Factor 1 [smoking cessation support behaviors], Factor 2 [smoking cessation support self-efficacy], Factor 3 [importance of smoking cessation support], and Factor 4 [beliefs about smoking cessation support] (hereafter, square brackets represent latent variables).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, our results also indicate that nurses with higher self-efficacy to engage in smoking counseling were more likely to implement smoking cessation interventions [ 19 , 22 , 25 ]. A previous study, in Japan, reported that research utilization competency was positively associated with self-efficacy and prenatal smoking cessation interventions among public health nurses [ 49 ]. Additionally, another study including 1054 primary healthcare nurses, in Sweden, reported that the ability and use of research were significant determinants of attitudes towards research and use of research findings [ 50 ].…”
Section: Discussionmentioning
confidence: 99%